Solid oxide electrolytic cell stack

By using M-doped Ni-based catalyst on the cathode of the solid oxide electrolytic cell stack and applying a protective coating composed of Ni, Ti, Nd, La, and Ce on the connecting plate, the problem of reducing the performance of the trace alkali metal elements on the stack is solved, and the corrosion resistance and overall performance of the stack are improved.

CN119615202AActive Publication Date: 2025-03-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411843148.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

When using solid oxide electrolytic cell stacks for high-temperature water vapor electrolysis, trace amounts of alkali metal elements and alkaline earth metal elements may be enriched on the surface of the nickel-based composite electrode, reducing the performance of the electrolytic cell and corroding the connecting plate, resulting in a degradation of the stack performance.

Method used

An M-doped Ni-based catalyst is used as the cathode electrocatalyst, and M is one or more of Na, K, Al, and Ti to form a nanoheterojunction to promote the adsorption of H2O molecules and reduce the H2O dissociation energy. At the same time, a protective coating is provided on the surface of the cathode runner of the connecting plate, and the coating is composed of Ni, Ti, Nd, La, and Ce to improve corrosion resistance.

Benefits of technology

It improves the cathode resistance and the overall performance of the stack, enhances the corrosion resistance to trace alkali metals, ensures the supply of reactants in the cathode electrochemical reaction area of ​​the electrolytic cell sheet, and extends the service life of the stack.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005188399510000011
    Figure HDA0005188399510000011
Patent Text Reader

Abstract

The invention discloses a solid oxide electrolytic cell galvanic pile which comprises a cathode collector plate, an anode collector plate, a sealing piece and a repeating unit which is located between the cathode collector plate and the anode collector plate and has trace alkali metal corrosion resistance, and the repeating unit comprises an electrolytic cell piece, a connecting plate, a power taking net 1 and a power taking net 2. The electric pile is particularly suitable for electrolysis of high-temperature water vapor containing trace alkali metal elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells and electrolytic cells, and in particular to a solid oxide electrolytic cell stack. Background Art

[0002] Solid oxide electrolysis cell (SOEC) is an all-solid-state device that can directly convert heat and electricity into chemical energy in fuel at medium and high temperatures (700-850℃), which can be regarded as the reverse process of solid oxide fuel cell (SOFC). Compared with low-temperature water electrolysis hydrogen production technologies such as alkaline water electrolysis, SOEC high-temperature water vapor electrolysis hydrogen production has the following outstanding technical advantages: (1) SOEC electrical efficiency can reach 100%, and the system efficiency is expected to reach 90%, which is considered to be the most efficient water electrolysis hydrogen production technology; (2) SOEC operates at high temperature and does not require the use of precious metal catalysts. It mainly uses perovskite-type rare earth oxide catalysts, which has lower material costs; (3) SOEC is an all-solid-state structure, which is safer and more reliable; (4) In chemical, metallurgical, steelmaking and other processes that generate high-temperature water vapor and waste heat, SOEC can directly couple and utilize these high-temperature heat sources to produce green hydrogen by electrolysis, which is more conducive to the low-carbon transformation of the industry and has broad application prospects.

[0003] Industrial water vapor may contain trace amounts of alkali metal elements and alkaline earth metal elements. When SOEC stacks use this water vapor for direct electrolysis, it will be enriched on the surface of traditional nickel-based composite electrodes, occupying active sites and reducing the performance of the electrolytic cell. It may also corrode the connecting plate, resulting in reduced stack performance. Therefore, it is necessary to develop an electrolytic stack suitable for feed containing trace amounts of alkali metal water vapor. Summary of the invention

[0004] The present invention provides a solid oxide electrolytic cell stack, comprising an anode current collecting plate, a cathode current collecting plate, a sealing member and a repeating unit located between the anode current collecting plate and the cathode current collecting plate.

[0005] The repeating unit includes a power grid 1, an electrolytic cell sheet, a power grid 2 and a connecting plate in sequence;

[0006] The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence. The cathode is a composite cathode composed of an electrocatalyst and an electrolyte. The electrocatalyst is a Ni-based catalyst doped with M, where M is one or more of Na, K, Al and Ti; and the molar ratio of M to Ni is 20:80 to 0.01:99.99.

[0007] The two surfaces of the connecting plate are respectively provided with an anode flow channel and a cathode flow channel, and the surfaces of the anode flow channel and the cathode flow channel are provided with a protective coating, and the cathode flow channel coating is composed of Ni, Ti, Nd, La, and Ce; the coating mass content is 90-99% Ni, 0.01-1% Ti, 0.01-5% Nd, 0.01-2% La, and 0.01-2% Ce;

[0008] The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet;

[0009] The assembly order of the battery stack is cathode collector plate, repeating unit (grid 1, electrolytic cell sheet, grid 2 and connecting plate), seal, repeating unit (grid 1, electrolytic cell sheet, grid 2 and connecting plate), during the packaging process, the anode of the electrolytic cell sheet is connected to the anode flow channel of the connecting plate, the cathode of the electrolytic cell sheet is connected to the cathode flow channel of the connecting plate, the anode current collector plate and the connecting plate are connected by a seal, and the connecting plate and the anode current collector plate, and the connecting plate and the cathode current collector plate are connected by laser welding.

[0010] Furthermore, in the above technical solution, the preparation of the composite cathode comprises the following steps:

[0011] The cathode electrocatalyst of the electrolytic cell sheet is prepared by a co-precipitation method combined with an impregnation method. A nickel salt solution is dripped into a precipitant solution to form a precipitate. The precipitate is washed and dried, and heat-treated at 200-450° C. in a muffle furnace for 1-10 hours to obtain NiO. A mixed aqueous solution of M salt is dripped onto the surface of NiO, dried at 60-90° C. in an oven for 10-24 hours, and then calcined at 200-500° C. for 5 hours to form a cathode electrocatalytic precursor. The definition of M is the same as above. The cathode electrocatalytic precursor and the electrolyte mixture are used as a mixed cathode precursor, and a composite cathode of an electrocatalyst and an electrolyte is formed after reduction at 750° C. The amount ratio of the cathode electrocatalytic precursor to the electrolyte is 0.7:0.3-0.4:0.6.

[0012] Furthermore, in the above technical solution, the electrolyte is YSZ.

[0013] Furthermore, in the above technical solution, the precipitant is any one of NH4HCO3, Na2CO3, NaHCO3, and urea.

[0014] Furthermore, in the above technical solution, the preparation method of the cathode flow channel surface protective coating of the connecting plate is to prepare it by magnetron sputtering according to the element content, and the sputtering power is 20 to 70 Wcm -2 , the sputtering substrate temperature is 100-300°C, and the sputtering time is 2-10h.

[0015] Furthermore, in the above technical solution, the thickness of the protective coating on the surface of the cathode flow channel of the connecting plate is 0.1 to 10 microns.

[0016] Furthermore, in the above technical solution, the thickness of the protective coating on the surface of the anode channel of the connecting plate is 0.1 to 10 microns, and the coating is (Mn, Co) 3 O 4 .

[0017] Furthermore, in the above technical solution, the number of the repeating unit is at least 1, for example 2-30, or 4-10.

[0018] Furthermore, in the above technical solution, the cathode current collecting plate and the adjacent repeating units do not have a connecting plate, and the cathode current collecting plate is connected to the power grid 2 in the adjacent repeating unit; the anode current collecting plate is connected to the power grid 1 in the adjacent repeating unit.

[0019] The advantages of the present invention are:

[0020] (1) The cathode electrocatalyst of the electrolytic cell sheet used in the solid oxide electrolytic cell stack of the present invention is a Ni-based catalyst doped with M, where M is one or more of Na, K, Al, and Ti. M can form a nano-heterojunction with Ni, thereby promoting the adsorption of H2O molecules and reducing the dissociation energy of H2O. At the same time, the electrocatalyst weakens the adsorption and enrichment of alkali metals and alkaline earth metals in steam on the cathode surface, thereby improving the tolerance of the cathode.

[0021] (2) The cathode flow channel surface of the connecting plate of the solid oxide electrolytic cell stack of the present invention is provided with a protective coating, which is composed of Ni, Ti, Nd, La, and Ce, with a Ni mass content of not less than 90%. The elements such as Nd, La, and Ce promote low-temperature densification of the coating and improve corrosion resistance.

[0022] (3) During the long-term electrolysis of water vapor, trace alkali metals in the water vapor feed may deposit and scale on the surface of the cathode flow channel of the connecting plate, increasing the water vapor mass transfer resistance, failing to meet the requirements of the cathode water vapor dissociation reaction, and resulting in reduced stack performance. The solid oxide electrolytic cell stack of the present invention uses a coated connecting plate, which effectively improves the corrosion resistance of the power grid and the connecting plate, ensures the supply of reactants in the cathode electrochemical reaction zone of the electrolytic cell sheet, and improves the stack performance.

[0023] (4) The present invention provides the fuel cell stack with the ability to resist corrosion by trace alkali metals by configuring the cathode catalyst, the connecting plate and the power grid. When the fuel cell stack contacts high-temperature steam containing trace alkali metals, the fuel cell stack exhibits excellent structural stability. This is due to the cathode catalyst having a high ability to dissociate water molecules and the anti-corrosion coating on the surface of the connecting plate and the power grid.

[0024] (5) The solid oxide electrolytic cell stack of the present invention is particularly suitable for direct feeding of high-temperature steam in the steel industry, avoiding the steam condensation and purification process, reducing the cost for large-scale hydrogen production, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the stack structure of the solid oxide electrolytic cell of the present invention. DETAILED DESCRIPTION

[0026] The present invention will be further described below by way of examples.

[0027] Embodiment 1:

[0028] A solid oxide electrolytic cell stack, see attached Figure 1 , comprising an anode current collecting plate 2, a cathode current collecting plate 1, a seal 6 and a repeating unit 3 located between the anode current collecting plate 2 and the cathode current collecting plate 1, wherein the repeating unit comprises a power grid 1 7, an electrolytic cell sheet 4, a power grid 2 8 and a connecting plate 5 in sequence; the cathode current collecting plate is provided with a cathode flow channel, and the anode current collecting plate is provided with an anode flow channel; the cathode current collecting plate and the adjacent repeating unit do not contain a connecting plate, and the cathode current collecting plate is connected to the power grid 2 8 in the adjacent repeating unit; the anode current collecting plate is connected to the power grid 1 in the adjacent repeating unit.

[0029] The two surfaces of the connecting plate 5 are respectively provided with an anode flow channel and a cathode flow channel. The surface of the cathode flow channel is provided with a 1 micron cathode protective coating 9, which is 95wt% Ni, 0.5wt% Ti, 3.5wt% Nd, 0.5wt% La, and 0.5wt% Ce. The cathode coating is prepared by magnetron sputtering with a sputtering power of 50Wcm -2 The sputtering substrate temperature is 150°C, the sputtering time is 3h, and a 1-micron anode protective coating MnCo2O4 10 is provided on the surface of the anode channel.

[0030] The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet 4. The power grid 1 is a stainless steel 441 mesh, and the power grid 2 is a Ni mesh.

[0031] During the packaging process, the anode of the electrolytic cell sheet is connected to the anode flow channel of the connecting plate, the cathode of the electrolytic cell sheet is connected to the cathode flow channel of the connecting plate, the connecting plates are connected by seals, and the connecting plate and the anode current collecting plate, and the connecting plate and the cathode current collecting plate are welded by laser.

[0032] The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence. The electrocatalyst of the cathode of the electrolytic cell sheet is 0.2at%K-0.2%atNa-99.6at%Ni, the cathode is a composite of the cathode electrocatalyst and YSZ (8mol%Y2O3 doped ZrO2), the mass fraction of YSZ is 55%, the electrolyte is YSZ, and the anode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3-Gd 0.1 Ce 0.9 O2, with a 0.5 μm Gd separation layer between the cathode and the electrolyte 0.1 Ce 0.9 O2.

[0033] Among them, the cathode electrocatalyst was prepared by a co-precipitation method combined with an impregnation method. 0.996 mol of Ni(NO3)2.6H2O was dissolved in deionized water to form a 0.5 mol / L nickel nitrate solution. A 0.5 M NH4HCO3 solution was used as a precipitant. The nickel nitrate solution was added dropwise to the NH4HCO3 solution to gradually form a precipitate. The precipitate was repeatedly washed three times by suction filtration, dried in an oven (90°C) for 24 hours, and heat treated at 350°C in a muffle furnace for 5 hours to obtain NiO. 0.002 mol KNO3 and 0.002 mol NaNO3 were dissolved in 4 mL of deionized water to form a mixed aqueous solution, the mixed aqueous solution was dropped onto the NiO surface, dried in an oven (90°C) for 24 h, and then calcined at 300°C for 5 h to form a cathode electrocatalytic precursor, and a mixture of 0.6 g of the cathode electrocatalytic precursor and 0.4 g of YSZ was used as a mixed cathode precursor, which was reduced at 750°C to form a composite cathode of electrocatalyst (0.2 at% K-0.2% atNa-99.6 at% Ni) and YSZ.

[0034] When the stack uses a simulated water sample (containing 5wt% Na2CO3) as feed to produce hydrogen by electrolysis, the stack temperature is 750°C, the stack electrolysis voltage is 13V, and the electrolysis current reaches 53.66A.

[0035] Example 2

[0036] A solid oxide electrolytic cell stack comprises an anode current collecting plate, a cathode current collecting plate, a seal and a repeating unit located between the anode current collecting plate and the cathode current collecting plate, wherein the repeating unit comprises an electricity grid 1, an electrolytic cell sheet, an electricity grid 2 and a connecting plate in sequence; the cathode current collecting plate is provided with a cathode flow channel, and the anode current collecting plate is provided with an anode flow channel; the cathode current collecting plate and the adjacent repeating unit do not contain a connecting plate, the cathode current collecting plate is connected to the electricity grid 2 in the adjacent repeating unit; the anode current collecting plate is connected to the electricity grid 1 in the adjacent repeating unit.

[0037] The two surfaces of the connecting plate are provided with an anode flow channel and a cathode flow channel respectively. The surface of the cathode flow channel is provided with a 1 micron cathode protective coating. The cathode coating is 95wt% Ni, 0.5wt% Ti, 3.5wt% Nd, 0.5wt% La, and 0.5wt% Ce. The cathode coating is prepared by magnetron sputtering with a sputtering power of 50Wcm -2 The sputtering substrate temperature is 150℃, the sputtering time is 3h, and the anode channel surface is provided with a 1-micron anode protective coating MnCo2O4.

[0038] The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet. The power grid 1 is a stainless steel 441 mesh, and the power grid 2 is a Ni mesh.

[0039] During the packaging process, the anode of the electrolytic cell sheet is connected to the anode flow channel of the connecting plate, the cathode of the electrolytic cell sheet is connected to the cathode flow channel of the connecting plate, the connecting plates are connected by seals, and the connecting plate and the anode current collecting plate, and the connecting plate and the cathode current collecting plate are welded by laser.

[0040] The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence. The electrocatalyst of the cathode of the electrolytic cell sheet is 0.2 at% K-0.8 at% Na-99 at% Ni, the cathode is a composite of the cathode electrocatalyst and YSZ (8 mol% Y2O3 doped ZrO2), the electrolyte is YSZ, and the anode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3-Gd 0.1 Ce 0.9 O2, with a 0.5 μm Gd separation layer between the cathode and the electrolyte 0.1 Ce 0.9 O2.

[0041] Among them, the cathode electrocatalyst was prepared by a co-precipitation method combined with an impregnation method. 0.99 mol of Ni(NO3)2.6H2O was dissolved in deionized water to form a 0.5 mol / L nickel nitrate solution. A 0.5 M NH4HCO3 solution was used as a precipitant. The nickel nitrate solution was added dropwise to the NH4HCO3 solution to gradually form a precipitate. The precipitate was repeatedly washed three times by suction filtration, dried in an oven (90°C) for 24 hours, and heat treated at 350°C in a muffle furnace for 5 hours to obtain NiO. 0.002 mol KNO3 and 0.008 mol NaNO3 were dissolved in 10 mL of deionized water to form a mixed aqueous solution, the mixed aqueous solution was dropped onto the NiO surface, dried in an oven (90°C) for 24 h, and then calcined at 300°C for 5 h to form a cathode electrocatalytic precursor, and a mixture of 0.6 g of the cathode electrocatalytic precursor and 0.4 g of YSZ was used as a mixed cathode precursor, which was reduced at 750°C to form a composite cathode of electrocatalyst (0.2 at% K-0.8% atNa-99 at% Ni) and YSZ.

[0042] When the stack uses a simulated water sample (containing 5wt% Na2CO3) as feed to electrolyze hydrogen, the stack temperature is 750°C, the stack electrolysis voltage is 13V, the electrolysis current reaches 50.05A, and the change in the content of the elements that make up the electrocatalyst affects the stack performance.

[0043] Embodiment 3:

[0044] A solid oxide electrolytic cell stack comprises an anode current collecting plate, a cathode current collecting plate, a seal and a repeating unit located between the anode current collecting plate and the cathode current collecting plate, wherein the repeating unit comprises an electricity grid 1, an electrolytic cell sheet, an electricity grid 2 and a connecting plate in sequence; the cathode current collecting plate is provided with a cathode flow channel, and the anode current collecting plate is provided with an anode flow channel; the cathode current collecting plate and the adjacent repeating unit do not contain a connecting plate, the cathode current collecting plate is connected to the electricity grid 2 in the adjacent repeating unit; the anode current collecting plate is connected to the electricity grid 1 in the adjacent repeating unit.

[0045] The two surfaces of the connecting plate are provided with an anode flow channel and a cathode flow channel respectively. The surface of the cathode flow channel is provided with a 1 micron cathode protective coating. The cathode coating is 95wt% Ni, 0.5wt% Ti, 3.5wt% Nd, 0.5wt% La, and 0.5wt% Ce. The cathode coating is prepared by magnetron sputtering with a sputtering power of 50Wcm -2 The sputtering substrate temperature is 150℃, the sputtering time is 3h, and the anode channel surface is provided with a 1-micron anode protective coating MnCo2O4.

[0046] The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet. The power grid 1 is a stainless steel 441 mesh, and the power grid 2 is a Ni mesh.

[0047] During the packaging process, the anode of the electrolytic cell sheet is connected to the anode flow channel of the connecting plate, the cathode of the electrolytic cell sheet is connected to the cathode flow channel of the connecting plate, the connecting plates are connected by seals, and the connecting plate and the anode current collecting plate, and the connecting plate and the cathode current collecting plate are welded by laser.

[0048] The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence. The electrocatalyst of the cathode of the electrolytic cell sheet is 0.2at% K-0.8%atAl-99at%Ni, the cathode is a composite of the cathode electrocatalyst and YSZ (8mol% Y2O3 doped ZrO2), the electrolyte is YSZ, and the anode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3-Gd 0.1 Ce 0.9 O2, with a 0.5 μm Gd separation layer between the cathode and the electrolyte 0.1 Ce 0.9 O2.

[0049] Among them, the cathode electrocatalyst was prepared by a co-precipitation method combined with an impregnation method. 0.99 mol of Ni(NO3)2.6H2O was dissolved in deionized water to form a 0.5 mol / L nickel nitrate solution. A 0.5 M NH4HCO3 solution was used as a precipitant. The nickel nitrate solution was added dropwise to the NH4HCO3 solution to gradually form a precipitate. The precipitate was repeatedly washed three times by suction filtration, dried in an oven (90°C) for 24 hours, and heat treated at 350°C in a muffle furnace for 5 hours to obtain NiO. 0.002 mol KNO3 and 0.008 mol Al(NO3)3 were dissolved in 10 mL of deionized water to form a mixed aqueous solution, the mixed aqueous solution was dropped onto the NiO surface, dried in an oven (90°C) for 24 h, and then calcined at 300°C for 5 h to form a cathode electrocatalytic precursor, and a mixture of 0.6 g of the cathode electrocatalytic precursor and 0.4 g of YSZ was used as a mixed cathode precursor, which was reduced at 750°C to form a composite cathode of electrocatalyst (0.2 at% K-0.8% atAl-99 at% Ni) and YSZ.

[0050] When the stack uses a simulated water sample (containing 5wt% Na2CO3) as feed to electrolyze hydrogen, the stack temperature is 750°C, the stack electrolysis voltage is 13V, the electrolysis current reaches 49.95A, and the change in the content of the elements that make up the electrocatalyst affects the stack performance.

[0051] Embodiment 4:

[0052] A solid oxide electrolytic cell stack comprises an anode current collecting plate, a cathode current collecting plate, a seal and a repeating unit located between the anode current collecting plate and the cathode current collecting plate, wherein the repeating unit comprises an electricity grid 1, an electrolytic cell sheet, an electricity grid 2 and a connecting plate in sequence; the cathode current collecting plate is provided with a cathode flow channel, and the anode current collecting plate is provided with an anode flow channel; the cathode current collecting plate and the adjacent repeating unit do not contain a connecting plate, the cathode current collecting plate is connected to the electricity grid 2 in the adjacent repeating unit; the anode current collecting plate is connected to the electricity grid 1 in the adjacent repeating unit.

[0053] The two surfaces of the connecting plate are provided with an anode flow channel and a cathode flow channel respectively. The surface of the cathode flow channel is provided with a 1 micron cathode protective coating. The cathode coating is 98.5wt% Ni, 0.1wt% Ti, 1.2wt% Nd, 0.1wt% La, and 0.1wt% Ce. The cathode coating is prepared by magnetron sputtering with a sputtering power of 50Wcm -2 The sputtering substrate temperature is 150℃, the sputtering time is 3h, and the anode channel surface is provided with a 1-micron anode protective coating MnCo2O4.

[0054] The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet. The power grid 1 is a stainless steel 441 mesh, and the power grid 2 is a Ni mesh.

[0055] During the packaging process, the anode of the electrolytic cell sheet is connected to the anode flow channel of the connecting plate, the cathode of the electrolytic cell sheet is connected to the cathode flow channel of the connecting plate, the connecting plates are connected by seals, and the connecting plate and the anode current collecting plate, and the connecting plate and the cathode current collecting plate are welded by laser.

[0056] The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence. The electrocatalyst of the cathode of the electrolytic cell sheet is 0.2 at% K-0.8 at% Na-99 at% Ni, the cathode is a composite of the cathode electrocatalyst and YSZ (8 mol% Y2O3 doped ZrO2), the electrolyte is YSZ, and the anode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3-Gd 0.1 Ce 0.9 O2, with a 0.5 μm Gd separation layer between the cathode and the electrolyte 0.1 Ce 0.9 O2.

[0057] Among them, the cathode electrocatalyst was prepared by a co-precipitation method combined with an impregnation method. 0.99 mol of Ni(NO3)2.6H2O was dissolved in deionized water to form a 0.5 mol / L nickel nitrate solution. A 0.5 M NH4HCO3 solution was used as a precipitant. The nickel nitrate solution was added dropwise to the NH4HCO3 solution to gradually form a precipitate. The precipitate was repeatedly washed three times by suction filtration, dried in an oven (90°C) for 24 hours, and heat treated at 350°C in a muffle furnace for 5 hours to obtain NiO. 0.002 mol KNO3 and 0.008 mol NaNO3 were dissolved in 10 mL of deionized water to form a mixed aqueous solution, the mixed aqueous solution was dropped onto the NiO surface, dried in an oven (90°C) for 24 h, and then calcined at 300°C for 5 h to form a cathode electrocatalytic precursor, and a mixture of 0.6 g of the cathode electrocatalytic precursor and 0.4 g of YSZ was used as a mixed cathode precursor, which was reduced at 750°C to form a composite cathode of electrocatalyst (0.2 at% K-0.8% atNa-99 at% Ni) and YSZ.

[0058] When the stack uses a simulated water sample (containing 5wt% Na2CO3) as feed to electrolyze hydrogen, the stack temperature is 750°C, the stack electrolysis voltage is 13V, the electrolysis current reaches 51.23A, and the change in the content of the elements that make up the electrocatalyst affects the stack performance.

[0059] Comparative Example 1:

[0060] A solid oxide electrolytic cell stack comprises an anode current collecting plate, a cathode current collecting plate, a seal and a repeating unit located between the anode current collecting plate and the cathode current collecting plate, wherein the repeating unit comprises an electricity grid 1, an electrolytic cell sheet, an electricity grid 2 and a connecting plate in sequence; the cathode current collecting plate is provided with a cathode flow channel, and the anode current collecting plate is provided with an anode flow channel; the cathode current collecting plate and the adjacent repeating unit do not contain a connecting plate, the cathode current collecting plate is connected to the electricity grid 2 in the adjacent repeating unit; the anode current collecting plate is connected to the electricity grid 1 in the adjacent repeating unit.

[0061] An anode flow channel and a cathode flow channel are respectively arranged on the two surfaces of the connecting plate, and a 1-micron anode protective coating MnCo2O4 is arranged on the surface of the anode flow channel.

[0062] The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet. The power grid 1 is a stainless steel 441 mesh, and the power grid 2 is a Ni mesh.

[0063] During the packaging process, the anode of the electrolytic cell sheet is connected to the anode flow channel of the connecting plate, the cathode of the electrolytic cell sheet is connected to the cathode flow channel of the connecting plate, the connecting plates are connected by seals, and the connecting plate and the anode current collecting plate, and the connecting plate and the cathode current collecting plate are welded by laser.

[0064] The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence. The electrocatalyst of the cathode of the electrolytic cell sheet is Ni, the cathode is a composite of the cathode electrocatalyst and YSZ (8 mol% Y2O3 doped ZrO2), the mass fraction of YSZ is 55%, the electrolyte is YSZ, and the anode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3-Gd 0.1 Ce 0.9 O2, with a 0.5 μm Gd separation layer between the cathode and the electrolyte 0.1 Ce 0.9 O2.

[0065] When the stack uses a simulated water sample (containing 5wt% Na2CO3) as feed to produce hydrogen through electrolysis, the stack temperature is 750°C and the stack electrolysis voltage is 13V, and the electrolysis current reaches 43.72A. Comparative Example 2:

[0066] A solid oxide electrolytic cell stack comprises an anode current collecting plate, a cathode current collecting plate, a seal and a repeating unit located between the anode current collecting plate and the cathode current collecting plate, wherein the repeating unit comprises an electricity grid 1, an electrolytic cell sheet, an electricity grid 2 and a connecting plate in sequence; the cathode current collecting plate is provided with a cathode flow channel, and the anode current collecting plate is provided with an anode flow channel; the cathode current collecting plate and the adjacent repeating unit do not contain a connecting plate, the cathode current collecting plate is connected to the electricity grid 2 in the adjacent repeating unit; the anode current collecting plate is connected to the electricity grid 1 in the adjacent repeating unit.

[0067] The two surfaces of the connecting plate are provided with an anode flow channel and a cathode flow channel respectively. The surface of the cathode flow channel is provided with a 1 micron cathode protective coating. The cathode coating is 95wt% Ni, 0.5wt% Ti, 3.5wt% Nd, 0.5wt% La, and 0.5wt% Ce. The cathode coating is prepared by magnetron sputtering with a sputtering power of 50Wcm -2 The sputtering substrate temperature is 150°C and the sputtering time is 3h; the surface of the anode channel is provided with a 1-micron anode protective coating MnCo2O4.

[0068] The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet. The power grid 1 is a stainless steel 441 mesh, and the power grid 2 is a Ni mesh.

[0069] During the packaging process, the anode of the electrolytic cell sheet is connected to the anode flow channel of the connecting plate, the cathode of the electrolytic cell sheet is connected to the cathode flow channel of the connecting plate, the connecting plates are connected by seals, and the connecting plate and the anode current collecting plate, and the connecting plate and the cathode current collecting plate are welded by laser.

[0070] The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence. The electrocatalyst of the cathode of the electrolytic cell sheet is Ni, the cathode is a composite of the cathode electrocatalyst and YSZ (8 mol% Y2O3 doped ZrO2), the mass fraction of YSZ is 55%, the electrolyte is YSZ, and the anode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3-Gd 0.1 Ce 0.9 O2, with a 0.5 μm Gd separation layer between the cathode and the electrolyte 0.1 Ce 0.9 O2.

[0071] When the stack uses a simulated water sample (containing 5wt% Na2CO3) as feed to produce hydrogen by electrolysis, the stack temperature is 750°C, the stack electrolysis voltage is 13V, and the electrolysis current reaches 47.02A.

[0072] Comparative Example 3:

[0073] A solid oxide electrolytic cell stack comprises an anode current collecting plate, a cathode current collecting plate, a seal and a repeating unit located between the anode current collecting plate and the cathode current collecting plate, wherein the repeating unit comprises an electricity grid 1, an electrolytic cell sheet, an electricity grid 2 and a connecting plate in sequence; the cathode current collecting plate is provided with a cathode flow channel, and the anode current collecting plate is provided with an anode flow channel; the cathode current collecting plate and the adjacent repeating unit do not contain a connecting plate, the cathode current collecting plate is connected to the electricity grid 2 in the adjacent repeating unit; the anode current collecting plate is connected to the electricity grid 1 in the adjacent repeating unit.

[0074] The two surfaces of the connecting plate are provided with an anode flow channel and a cathode flow channel respectively. The surface of the cathode flow channel is provided with a 1 micron cathode protective coating. The cathode coating is 95wt% Ni, 0.5wt% Ti, 3.5wt% Nd, 0.5wt% La, and 0.5wt% Ce. The cathode coating is prepared by magnetron sputtering with a sputtering power of 50Wcm -2 The sputtering substrate temperature is 150°C, the sputtering time is 3h, and a 1-micron anode protective coating MnCo2O4 is provided on the surface of the anode channel.

[0075] The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet. The power grid 1 is a stainless steel 441 mesh, and the power grid 2 is a Ni mesh.

[0076] During the packaging process, the anode of the electrolytic cell sheet is connected to the anode flow channel of the connecting plate, the cathode of the electrolytic cell sheet is connected to the cathode flow channel of the connecting plate, the connecting plates are connected with seals, and the connecting plate and the anode current collecting plate, and the connecting plate and the cathode current collecting plate are welded by laser.

[0077] The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence. The electrocatalyst of the cathode of the electrolytic cell sheet is 0.2 at% K-0.2 at% Mg-99.6 at% Ni, the cathode is a composite of the cathode electrocatalyst and YSZ (8 mol% Y2O3 doped ZrO2), the electrolyte is YSZ, and the anode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3-Gd 0.1 Ce 0.9 O2, with a 0.5 μm Gd separation layer between the cathode and the electrolyte 0.1 Ce 0.9 O2.

[0078] Among them, the cathode electrocatalyst was prepared by a co-precipitation method combined with an impregnation method. 0.996 mol of Ni(NO3)2.6H2O was dissolved in deionized water to form a 0.5 mol / L nickel nitrate solution. A 0.5 M NH4HCO3 solution was used as a precipitant. The nickel nitrate solution was added dropwise to the NH4HCO3 solution to gradually form a precipitate. The precipitate was repeatedly washed three times by suction filtration, dried in an oven (90°C) for 24 hours, and heat treated at 350°C in a muffle furnace for 5 hours to obtain NiO. 0.002 mol KNO3 and 0.002 mol Mg(NO3)2 were dissolved in 4 mL of deionized water to form a mixed aqueous solution, the mixed aqueous solution was dropped onto the NiO surface, dried in an oven (90°C) for 24 h, and then calcined at 800°C for 5 h to form a cathode electrocatalytic precursor, and a mixture of 0.6 g of the cathode electrocatalytic precursor and 0.4 g of YSZ was used as a mixed cathode precursor, which was reduced at 750°C to form a composite cathode of electrocatalyst (0.2 at% K-0.2% atMg-99.6 at% Ni) and YSZ.

[0079] When the stack uses a simulated water sample (containing 5wt% Na2CO3) as feed to electrolyze hydrogen, the stack temperature is 750°C, the stack electrolysis voltage is 13V, the electrolysis current reaches 48.76A, and the change in the components of the electrocatalyst causes a decrease in the stack performance.

[0080] Comparative Example 4:

[0081] A solid oxide electrolytic cell stack comprises an anode current collecting plate, a cathode current collecting plate, a seal and a repeating unit located between the anode current collecting plate and the cathode current collecting plate, wherein the repeating unit comprises an electricity grid 1, an electrolytic cell sheet, an electricity grid 2 and a connecting plate in sequence; the cathode current collecting plate is provided with a cathode flow channel, and the anode current collecting plate is provided with an anode flow channel; the cathode current collecting plate and the adjacent repeating unit do not contain a connecting plate, the cathode current collecting plate is connected to the electricity grid 2 in the adjacent repeating unit; the anode current collecting plate is connected to the electricity grid 1 in the adjacent repeating unit.

[0082] The two surfaces of the connecting plate are provided with an anode flow channel and a cathode flow channel respectively. The surface of the cathode flow channel is provided with a 1 micron cathode protective coating. The cathode coating is 95wt% Ni, 0.5wt% Ti, 3.5wt% Nd, 0.5wt% La, and 0.5wt% Ce. The cathode coating is prepared by magnetron sputtering with a sputtering power of 50Wcm -2 The sputtering substrate temperature is 150°C, the sputtering time is 3h, and a 1-micron anode protective coating MnCo2O4 is provided on the surface of the anode channel.

[0083] The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet. The power grid 1 is a stainless steel 441 mesh, and the power grid 2 is a Ni mesh.

[0084] During the packaging process, the anode of the electrolytic cell sheet is connected to the anode flow channel of the connecting plate, the cathode of the electrolytic cell sheet is connected to the cathode flow channel of the connecting plate, the connecting plates are connected by seals, and the connecting plate and the anode current collecting plate, and the connecting plate and the cathode current collecting plate are welded by laser.

[0085] The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence. The electrocatalyst of the cathode of the electrolytic cell sheet is 1 at% K-24 at% Mg-75 at% Ni, the cathode is a composite of the cathode electrocatalyst and YSZ (8 mol% Y2O3 doped ZrO2), the electrolyte is YSZ, and the anode is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3-Gd 0.1 Ce 0.9 O2, with a 0.5 μm Gd separation layer between the cathode and the electrolyte 0.1 Ce 0.9 O2.

[0086] Among them, the cathode electrocatalyst was prepared by a co-precipitation method combined with an impregnation method. 0.75 mol of Ni(NO3)2.6H2O was dissolved in deionized water to form a 0.5 mol / L nickel nitrate solution. A 0.5 M NH4HCO3 solution was used as a precipitant. The nickel nitrate solution was added dropwise to the NH4HCO3 solution to gradually form a precipitate. The precipitate was repeatedly washed three times by suction filtration, dried in an oven (90°C) for 24 hours, and heat treated at 350°C in a muffle furnace for 5 hours to obtain NiO. 0.01 mol KNO3 and 0.24 mol Mg(NO3)2 were dissolved in 250 mL of deionized water to form a mixed aqueous solution, the mixed aqueous solution was dropped onto the NiO surface, dried in an oven (90°C) for 24 h, and then calcined at 800°C for 5 h to form a cathode electrocatalytic precursor, and a mixture of 0.6 g of the cathode electrocatalytic precursor and 0.4 g of YSZ was used as a mixed cathode precursor, which was reduced at 750°C to form a composite cathode of electrocatalyst (1at% K-24% atMg-75at% Ni) and YSZ.

[0087] When the stack uses a simulated water sample (containing 5wt% Na2CO3) as feed to electrolyze hydrogen, the stack temperature is 750°C, the stack electrolysis voltage is 13V, the electrolysis current reaches 22.03A, and the change in the components of the electrocatalyst causes a decrease in the stack performance.

Claims

1. A solid oxide electrolytic cell stack, characterized in that: It includes an anode current collecting plate, a cathode current collecting plate, a seal and a repeating unit located between the anode current collecting plate and the cathode current collecting plate; The repeating unit includes a power grid 1, an electrolytic cell sheet, a power grid 2 and a connecting plate in sequence; The electrolytic cell sheet comprises an anode, an electrolyte and a cathode in sequence, wherein the cathode is a composite cathode composed of an electrocatalyst and an electrolyte, and the electrocatalyst is a Ni-based catalyst doped with M, wherein M is one or more of Na, K, Al and Ti; and the molar ratio of M to Ni is 20:80 to 0.01:99.99; The two surfaces of the connecting plate are respectively provided with an anode flow channel and a cathode flow channel, and the surfaces of the anode flow channel and the cathode flow channel are provided with a protective coating, and the cathode flow channel coating is composed of Ni, Ti, Nd, La, and Ce; the mass content of each component of the coating is 90-99% Ni, 0.01-1% Ti, 0.01-5% Nd, 0.01-2% La, and 0.01-2% Ce; The power grid 1 is adjacent to the anode of the electrolytic sheet, and the power grid 2 is adjacent to the cathode of the electrolytic sheet.

2. The solid oxide electrolytic cell stack according to claim 1, characterized in that: The preparation of the composite cathode includes the following steps: A nickel salt solution is added dropwise to a precipitant solution to form a precipitate, the precipitate is washed and dried, and heat-treated at 200-450° C. in a muffle furnace for 1-10 hours to obtain NiO; a mixed aqueous solution of M salt is added dropwise to the surface of NiO, dried at 60-90° C. in an oven for 10-24 hours, and then calcined at 200-500° C. for 5 hours to form a cathode electrocatalytic precursor; the definition of M is the same as that of claim 1; A cathode electrocatalytic precursor and an electrolyte mixture are used as a mixed cathode precursor, and a composite cathode of an electrocatalyst and an electrolyte is formed after reduction at 750° C. The dosage ratio of the cathode electrocatalytic precursor to the electrolyte is 0.7:0.3 to 0.4:0.

6.

3. The solid oxide electrolytic cell stack according to claim 1 or 2, characterized in that: The electrolyte is YSZ.

4. The solid oxide electrolytic cell stack according to claim 2, characterized in that: The precipitant is any one of NH4HCO3, Na2CO3, NaHCO3 and urea.

5. The solid oxide electrolytic cell stack according to claim 1, characterized in that: The preparation method of the cathode flow channel surface protective coating of the connecting plate is magnetron sputtering, and the sputtering power is 20-70Wcm -2 , the sputtering substrate temperature is 100-300°C, and the sputtering time is 2-10h.

6. The solid oxide electrolytic cell stack according to claim 1, characterized in that: The thickness of the protective coating on the cathode flow channel surface of the connecting plate is 0.1 to 10 microns.

7. The solid oxide electrolytic cell stack according to claim 1, characterized in that: The protective coating on the surface of the anode flow channel of the connecting plate has a thickness of 0.1 to 10 microns, and the coating is (Mn, Co) 3 O 4 .

8. The solid oxide electrolytic cell stack according to claim 1, characterized in that: The number of the repeating unit is at least 1.

9. The solid oxide electrolytic cell stack according to claim 1, characterized in that: The cathode current collecting plate and the adjacent repeating units do not have a connecting plate, and the cathode current collecting plate is connected to the power grid 2 in the adjacent repeating units; the anode current collecting plate is connected to the power grid 1 in the adjacent repeating units.

Citation Information

Patent Citations

  • High performance cathodes for water electrolysers

    CN101925694A

  • Low-temperature online densification method of fuel cell electrolyte

    CN110224146A

  • Nano composite cathode as well as preparation and application thereof

    CN111244470A

  • Zirconium-based anode-supported solid oxide battery without isolating layer

    CN113258111A

  • Surface modification method of perovskite oxide cathode and application of perovskite oxide cathode in solid oxide electrolytic tank

    CN118291993A